Esthetic plastic surgery: Experiencies concerning corporal (re) constructions and implications for nursing - Voese, Carla Fernanda; Kleinpaul, William Vinicius; Petry, Analidia Rodolpho (Rev Rene, 2015)
Objective: to identify reasons which lead healthy subjects to search, for the first time, surgical methods for corporal modifications. Methods: it is a descriptive, exploratory and qualitative study. Data were collected through semi-structured interviews which were recorded. The interviews were made with eight women and resulted into four analytic categories. Results: the reasons which took healthy subjects to face surgical risks are regarding the improvement of the satisfaction with their own corporal image aiming at reaching a higher social insertion. It was observed that dissatisfaction concerning physical appearance was generated by inherited characteristics or by marks left after pregnancy. Financial cost, fear and family support, can make the decision to undergo the surgery difficult. Conclusion: the plastic surgery can promote the regain of self-esteem in the subject who makes the surgery.